2020
DOI: 10.3389/fpls.2020.606259
|View full text |Cite
|
Sign up to set email alerts
|

Floral Color Variation in Drosera cistiflora Is Associated With Switches in Beetle Pollinator Assemblages

Abstract: Floral color shifts are thought to be one of the most common evolutionary transitions in plants, and pollinators are often proposed as important selective agents driving these transitions. However, shifts in flower color can also be related to neutral genetic processes or pleiotropy linked with selection via other biotic agents or abiotic factors. Here we ask whether abiotic factors or pollinators provide the best explanation for divergence in flower color among populations of the sundew Drosera ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…2015; Smith 2016; Johnson et al . 2020). In fact, pollinator‐mediated selection on other flower traits ( i.e .…”
Section: Discussionmentioning
confidence: 99%
“…2015; Smith 2016; Johnson et al . 2020). In fact, pollinator‐mediated selection on other flower traits ( i.e .…”
Section: Discussionmentioning
confidence: 99%
“…While the lack of a clear association with abiotic factors points to a biotic explanation for the evolutionary divergence in flower color among populations, the role of pollinators as drivers of the color change in G. aurantiaca is not entirely clear. Pollination studies have shown that a single hopliine scarab beetle species, E. vulpina, is responsible for the majority of all floral visits to G. aurantiaca (Johnson et al, 2004), unlike the color polymorphic Drosera cistiflora in the western Cape region of South Africa, where several different species of hopliine scarab beetles discriminate between different color forms in the same population (Johnson et al, 2020). Our study did not provide clear evidence that E. vulpina beetles prefer any particular capitulum color within a population as they were recorded visiting capitula in both the red and yellow-flowered populations, and they did not appear to discriminate between G. aurantiaca color morphs at the northern color polymorphic RH site.…”
Section: Discussionmentioning
confidence: 99%
“…Geographical variation in the availability of pollinators with different color preferences would be expected to lead to intraspecific divergence in flower color among plant populations (Stebbins, 1970). For example, the floral color polymorphism in Drosera cistiflora may be accounted for by the spatiotemporal variation in pollinator assemblages which display different color preferences (Johnson et al, 2020). This micro-evolutionary process could account for macro-evolutionary pattern if populations that differ in flower color were to diverge to the point of speciation (Johnson, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intriguingly, they found no clear association between morph color and any of the studied parameters. This contrasts with the case of colorpolymorphic South-African Drosera cistiflora that is pollinated by related hopliine beetles (Johnson et al, 2020;von Witt et al, 2020). It seems unlikely that the color polymorphism in G. aurantiaca is purely coincidental, but what other factor(s) (e.g., floral scent) may determine the geographic pattern remains a question that begs to be answered.…”
Section: Figurementioning
confidence: 91%